Internal Mechanisms of Human Motor Behaviour: A System-Theoretical Perspective - Petryński, Wacław; Staszkiewicz, Robert; Szyndera, Mirosław (Frontiers in Psychology, 2022)
The authors present the conceptual model of human motor behaviour. The movement is the only observable manifestation of all psychical processes; thus, it is the only phenomenon enabling the creation of hypotheses concerning psychological foundations of human behaviour. Moreover, in the field of biology and psychology, mathematical descriptions are not eligible, and appropriate seems to be a systemic approach. The authors present system of functional information processing modalities in the human mind (modalities’ ladder, basing on neurophysiological Bernstein’s theory), and the series of processes from stimuli reception to motor response execution (stream of consciousness). They make together a super-system. Its graphical representation may be termed “Column Diagram”. The authors analyse the functioning of this super-system in various intellectual-motor operations.